Effect of etchant containing an Urushiol monomer from lacquer sap on dentin biostability and bonding performance - Zhao, Ying; Xu, Xuanwen; Li, Lu; Zheng, Kai; Wang, Xiaoqian; Zhang, Ming; Xu, Yan (Frontiers in Bioengineering and Biotechnology, 2023)
Objectives. This study aimed to evaluate the effectiveness of urushiol as an additive to surface acid etchant on dentin structure by assessing the biostability of dentin and to determine the bonding strength of dentin and enamel to the composite in the complicated oral microecology. Methods. Etchants with different concentrations of urushiol (0.5, 1 or 3 wt%) were formulated and tested for their bonding performance. Demineralized dentin beams that were etched with experimental etchants were incubated in simulated body fluid (SBF) solutions by evaluating the weight decrement after 1 month. The effects of urushiol on dentin and matrix metalloproteinases (MMPs) were confirmed by scanning electron microscopy (SEM). Moreover, the antibiotic actions of urushiol on common cariogenic bacteria Streptococcus mutans, Streptococcus sanguinis, and Streptococcus gordonii as well as the biofilm were evaluated, and its effect on bacterial morphology was observed by SEM. At last, enamel and dentin specimens were prepared from human molars to determine the depth of demineralization by the etchants and the relation to the resin bond strengths to enamel and dentin (μTBS) and the morphology of the bonding interface. Results. Urushiol was capable of interacting with dentine and inhibiting collagenase activity, resulting in biostable dentine. Application of the etchants containing 0.5, 1 or 3 wt% urushiol significantly improved the durability of the dentin bonding interface with its instinct antibacterial property(P<0.05). Conclusion. Urushiol not only improves dentin stability by interacting with collagen and inactivating MMPs activity but also plays a role in antibacterial effects in the complicated oral microecology. The effectiveness of urushiol etchant prolongs the longevity of bonded dental restorations without compromising clinical operation time.